A performance profile of dairying in Bangladesh - programs, policies and way forwards (Bangladesh Journal of Animal Science, 2014)
A national dairy performance profile is developed and described in this article reviewing the performance of the smallholder dairy production system, its backward and forward supports and existing development programs and policies; and based on the analyses further way forwards are described concisely. Inclusion of quality genes over the past decades of crossbreeding resulted in crossbred cows of about 47% with an average lactation yield of 1838 litre in 266 days, while the similar performance of a local cow is 619 litre in 230 days, respectively. Further, population increase of crossbred cows may increase milk production horizontally at the expense of genetic dilution. Nevertheless, a common plane of nutrition with the availability of 54.7 and 22.5% of annual requirement of metabolizable energy and digestible crude protein, respectively, may not uphold vertical improvement of dairying in Bangladesh. Local buffaloes, on the other hand, having only 635 litre lactation yield in 227 days share only 2.29% of the total liquid milk production, and unlocking potentials of dairy Buffaloes may boost milk production further. Creation of an enabling environment for multiplication of private dairy feed  industry and community fodder production system; policy support to private entrepreneurs remain active in dairy marketing; reviewing and revising of present domestic support to dairy; establishment of easy credit and capital support to rural dairy farmers; strengthening of coordinated backward services of the public and private sector; capacity strengthening for dairy extension, research and education and human resource development are the way forwards for expediting the dairy industry in the country. An important and effective support to dairy would be capacity strengthening through establishing an autonomous organization for an enhanced coordinated support to both public and private sector with a clear authoritative mandate for setting policy priorities, institutional structures, priorities for research and extension and appropriation of adequate financial resources. Considering all the above suggestions an action plan may be formulated to meet the growing demand of milk in the present changing and challenging socio-economic condition of the country.DOI: http://dx.doi.org/10.3329/bjas.v43i2.20662 Bang. J. Anim. Sci. 2014. 43 (2): 81-103